A molecular network for functional versatility of HECATE transcription factors - Gaillochet, Christophe; Lohmann, Jan U. (The plant journal, 2018)
During the plant life cycle, diverse signaling inputs are continuously integrated and engage specific genetic programs depending on the cellular or developmental context. Consistent with an important role in this process, HECATE (HEC) basic helix-loop-helix transcription factors display diverse functions, from photomorphogenesis to the control of shoot meristem dynamics and gynoecium patterning. However, the molecular mechanisms underlying their functional versatility and the deployment of specific HEC subprograms remain elusive. To address this issue, we systematically identified proteins with the capacity to interact with HEC1, the best-characterized member of the family, and integrated this information with our data set of direct HEC1 target genes. The resulting core genetic modules were consistent with specific developmental functions of HEC1, including its described activities in light signaling, gynoecium development and auxin homeostasis. Importantly, we found that HEC genes also play a role in the modulation of flowering time, and uncovered that their role in gynoecium development may involve the direct transcriptional regulation of NGATHA1 (NGA1) and NGA2 genes. NGA factors were previously shown to contribute to fruit development, but our data now show that they also modulate stem cell homeostasis in the shoot apical meristem. Taken together, our results delineate a molecular network underlying the functional versatility of HEC transcription factors. Our analyses have not only allowed us to identify relevant target genes controlling shoot stem cell activity and a so far undescribed biological function of HEC1, but also provide a rich resource for the mechanistic elucidation of further context-dependent HEC activities.